The internationalization process of SMEs in the Latin American context: The Colombian case (2009)
Within the new world scheme and according to the challenges that a world each more globalized demands, it is imperative for companies to be prepared to initiate the internationalization process and to respond not only to the needs of a natural market as the local one, but also to those of the international market. Enterprises, especially the Small and Medium Enterprises (SMEs) and particularly in the Latin-American environment, keep being convinced that success is found in the local market but only a few start an internationalization process, while the rest of them remain in the exporting phase. A specific analysis was made to define the internationalization process which rules the Latin American enterprises specially the Colombian case. © Common Ground.